1992
DOI: 10.1007/bf02245126
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of diazepam and lorazepam on repetition priming in healthy volunteers

Abstract: The effects of two benzodiazepines, diazepam (15 or 20 mg orally) and lorazepam (1.75 or 2.5 mg orally), and a placebo on explicit memory, lexical priming and perceptual priming were assessed using a free-recall, a word-completion and a picture-completion test. The picture-completion test included two different study conditions intended to manipulate the magnitude of the priming effect. Sixty healthy volunteers took part in this double-blind study. Free-recall performances were altered by both drugs. Lorazepam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
34
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 42 publications
13
34
7
Order By: Relevance
“…At the chosen doses both drugs could be considered to be equally potent as evidenced by the equivalence of their effects upon sedation and explicit memory performance (see e.g. Dundee et al, 1979;Kothary et al, 1981;Sellal et al, 1992;Vidailhet et al, 1994). The time of administration was designed so that action peak of both drugs was achieved at the same time (1 hour after the intake of diazepam vs. 2 hours after the intake of lorazepam).…”
Section: Experimental Procedures and Drugssupporting
confidence: 42%
See 1 more Smart Citation
“…At the chosen doses both drugs could be considered to be equally potent as evidenced by the equivalence of their effects upon sedation and explicit memory performance (see e.g. Dundee et al, 1979;Kothary et al, 1981;Sellal et al, 1992;Vidailhet et al, 1994). The time of administration was designed so that action peak of both drugs was achieved at the same time (1 hour after the intake of diazepam vs. 2 hours after the intake of lorazepam).…”
Section: Experimental Procedures and Drugssupporting
confidence: 42%
“…Legrand et al, 1995;Sellal et al, 1992;Vidailhet et al, 1994) they have been shown to differ in their effects on visual perception. In particular, lorazepam, but not diazepam, has been shown to specifically facilitate the detection of a discontinuity between collinear contours (Beckers et al, 2001;Giersch, 1999Giersch, , 2001) resulting in the impaired integration of local visual information into global configurations (Giersch et al, 1997;Giersch & Lorenceau, 1999).…”
Section: Footnotesmentioning
confidence: 46%
“…Why both drugs exert such different effects is still not clear. It is not simply that lorazepam is more potent than diazepam as both drugs have similar negative effects on explicit memory (Sellal et al, 1992;Vidailhet et al, 1994;Legrand et al, 1995). Furthermore, diazepam has been shown to be more deleterious than lorazepam at certain occasions .…”
Section: Lorazepam Vs Diazepamcontrasting
confidence: 41%
“…These drugs differ, however, both on the performance levels for vernier offset discrimination and on masking effects. Differences between diazepam and lorazepam have previously been described concerning the identification of fragmented pictures (Vidailhet et al, 1994;Legrand et al, 1995;Wagemans et al, 1998), priming effects (Sellal et al, 1992;Vidailhet et al, 1994;Legrand et al, 1995), and detection of line discontinuities (Beckers et al, 2001). The link between the present findings and the effects of lorazepam on contour processing is supported by studies reporting an absence of effect of diazepam on the detection of line discontinuities (Beckers et al, 2001).…”
Section: Lorazepam Vs Diazepamcontrasting
confidence: 39%
“…The main effects of BZDs are well known; they include a sedative, an anxiolytic, a muscle relaxant, and an anticonvulsivant action. As regards their side effects, besides habituation (Woods et al, 1987), BZDs have been shown to have a detrimental influence on certain cognitive or perceptual abilities, such as memory (Clarke et al, 1970;Brown et al, 1982Brown et al, , 1989Knopman, 1991;Sellal et al, 1992) and attention (Johnson et al, 1995;Carter et al, 1998). However, none of these studies have involved the auditory sensory modality.…”
Section: Introductionsupporting
confidence: 43%